Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.3390/toxics9100248
|View full text |Cite
|
Sign up to set email alerts
|

Solid-Phase Partitioning and Leaching Behavior of Pb and Zn from Playground Soils in Kabwe, Zambia

Abstract: Zambia's Kabwe mine wastes (KMWs) are responsible for contaminating the surrounding soil and dust in the Kabwe district. Unfortunately, these wastes arise from the historical mining activities of lead (Pb) and Zinc (Zn), which lacked adequate waste management strategies. As a result, potentially toxic elements (PTEs) (Pb and Zn) spread across the Kabwe district. To assess the soil pollution derived from previous mining activities, we studied topsoil samples (n = 8) from the school playground soils (SPs). In th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…Soils at 12 sites within 20 km of the mine recorded a maximum of 113,801 mg / kg and a mean of 22,693 mg / kg (Zingani et al, 2020) (Table 1). Other studies reported maximum values in the order of tens of thousands of mg / kg and average values in the order of thousands of mg / kg (Ikenaka et al, 2010;Nakayama et al, 2011;Nakata et al, 2016;Uchida et al, 2017;Kříbek et al, 2019;Mwilola et al, 2020), except for the study by Mufalo et al (2021), which analyzed playground soils. Soil samples were likely collected from various locations, including residential areas, roadsides, agricultural land, and in the proximity of mines; however, detailed information on the location attributes of the data reported for the Kabwe region was mostly not provided.…”
Section: Environmental Pollution Statusmentioning
confidence: 99%
See 1 more Smart Citation
“…Soils at 12 sites within 20 km of the mine recorded a maximum of 113,801 mg / kg and a mean of 22,693 mg / kg (Zingani et al, 2020) (Table 1). Other studies reported maximum values in the order of tens of thousands of mg / kg and average values in the order of thousands of mg / kg (Ikenaka et al, 2010;Nakayama et al, 2011;Nakata et al, 2016;Uchida et al, 2017;Kříbek et al, 2019;Mwilola et al, 2020), except for the study by Mufalo et al (2021), which analyzed playground soils. Soil samples were likely collected from various locations, including residential areas, roadsides, agricultural land, and in the proximity of mines; however, detailed information on the location attributes of the data reported for the Kabwe region was mostly not provided.…”
Section: Environmental Pollution Statusmentioning
confidence: 99%
“…The extent of wind-induced diffusion in soil and mine waste is expected to depend on the particle size. Analysis of the particle size distribution of soil and Zn-leaching residue showed that 50% of the soil was less than 50 μm in diameter (Mufalo et al, 2021). The dumping site, which is the source of the Pb dispersion simulations, was covered with slag, and 6% of the slag was found to have a particle size smaller than 150 μm (Nakamura et al, 2021).…”
Section: Contamination Diffusion Pathways Meteorological Factor and P...mentioning
confidence: 99%
“…The powerful toxic effect that lead has on living organisms [ 120 , 121 ] is the reason why it is present in all international documents relating to its contents in the muscle tissues of fish and mussels, which are often the subject of human consumption. The recorded high values of Pb in all the tested samples clearly showed the presence of pollution in the studied ecosystems during this period.…”
Section: Content Of Pb and Zn In The Muscle Tissue Of Common Carp ( ...mentioning
confidence: 99%
“…Zinc plant leach residues (ZPLRs), especially those that were produced using old technologies, are regarded as environmental nuisances and hazardous wastes due to their high amounts of leachable residual hazardous elements such as Pb, Zn, cadmium (Cd), copper (Cu), and arsenic (As) [7][8][9][10]. Lead, Cd, and As can cause various illnesses that affect the central nervous system, skin, lungs and kidneys, even in minute amounts, while Cu and Zn are essential micronutrients that are toxic at high concentrations [11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…The dissolution of Pb and Zn under alkaline conditions is due to the formation of complexes with hydroxyl ions (OH − ) [21]. In weak to moderately strong alkaline solutions (i.e., pH [6][7][8][9][10][11][12], Pb and Zn dissolve as Pb(OH) 3 − with small amounts of Pb(OH) 4 2− and Zn(OH) 3 − with small amounts of Zn(OH) 4 2− , respectively. In a strong alkaline solution (i.e., pH > 12), the dominant species are Pb(OH) 4 2− for Pb and Zn(OH) 4 2− for Zn.…”
Section: Introductionmentioning
confidence: 99%